Binary Level Set Methods for Dynamic Reservoir Characterization by Operator Splitting Scheme (Advances in Applied Mathematics and Mechanics, 2021)
In this paper, operator splitting scheme for dynamic reservoircharacterization by binary level set method is employed. For this problem, the absolute permeability of the two-phase porous medium flow can be simulated by the constrained augmented Lagrangian optimization method with well data and seismic time-lapse data. By transforming the constrained optimization problem in an unconstrained one, thesaddle point problem can be solved by Uzawas algorithmswith operator splitting scheme, which is based on the essenceof binary level set method. Both the simple and complicatednumerical examples demonstrate that the given algorithms arestable  and efficient and the absolute permeability can besatisfactorily recovered.